THE EIGHTH GRADERS’ PERCEPTION ON SPEAKING ONLINE LEARNING DURING COVID-19 PANDEMIC IN SMP IT MISYKAT AL-ANWAR - Hasanah, Khofifah Indah (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
This research examines how students perceive online English learning as well as the advantages and disadvantages of online learning during the Covid 19 pandemic. Moreover, speaking skills require a lot of practice so that students are fluent in English. However, with the Covid-19 pandemic, all learning activities are carried out online. The problem of this research is how the students perceive online English learning and its advantages and disadvantages. The researchers used qualitative methods. Result of this research shows that learning to speak online through media such as Google Classroom, Google Meet, and Zoom makes students enjoy learning more because the material can be accessed from anywhere without having to come to school. The disadvantages are, that many students experienced material that was not conveyed, felt monotonous, and also that the network signal was inadequate for smooth learning.